IDENTIFIKASI MORFOLOGI DAN MORFOMETRI ORGANPENCERNAANSERTA SIFAT KUALITATIF WARNA BULU BELIBIS KEMBANG (Dendrocygna arcuata) DAN BELIBIS BATU (Dendrocygna javanica) - Nugraha Siwi (Jurnal Peternakan Integratif, 2014)
ABSTRACT Identification of morphology, morphometric andthe qualitative trait feather color is the basis of a selection process and breedingwhistling duck. This research aims to identify the main identifier on size and shape as well the qualitative nature of wandering (Dendrocygnaarcuata) and lesser whistling duck (Dendrocygnajavanica). The number of samples were studied was 10 head for each species. Data were analyzed using Principal Component Analysis with Software Statistical Package of Social Science,SPSS.The results showed that primary identifiersizemorphology forwandering (Dendrocygnaarcuata) and lesser whistling duck (Dendrocygnajavanica) was length of wing andtibia, while the identifier shapemorphology wasthird finger length and wing. The main identifiersizeof visceramorphometry was small intestine, while the main identifiershapeon large intestine for both. The main identifiersizeandshape of organs digestive tract is weight liver and ventricle, while the primary identifier shape isweight digestive organs are liver and small intestine weight. The different for qualitative trait of feather color in wandering whistling pduck has a thick black line from the head to neck and a thick white feather color on the back of the body to the tail, whilelesser whistling duck has a striking maroon red color on chest feathers.Conclusion, the morphologyand Visceramorphometry for wanderingis larger than lesser whistling duck. Keywords : Wandering whistling duck, lesser whistling duck, morphology, morphometric, qualitative trait. ABSTRAK   Identifikasi terhadap morfologi, morfometri dan sifat kualitatif warna bulu merupakan dasar dari beberapa proses seleksi dan pemuliaan burung belibis. Tujuan penelitian ini untuk mengidentifikasi penciri utama ukuran dan bentuk serta sifat kualitatif warna bulu belibis kembang (Dendrocygna arcuata) dan belibis batu (Dendrocygna javanica).Sampel yang diteliti sebanyak 10 ekor setiap species.Data dianalisis menggunakan Analisis Komponen Utama dengan bantuan Software Statistical Package Sosial Science, SPSS.Hasilpenelitianmenunjukkanbahwapenciriutamaukuranmorflogibelibis kembang(Dendrocygnaarcuata)danbelibisbatu(Dendrocygnajavanica)adalahpanjangsayapdanpanjang